Evaluación de técnica dependientes para el análisis forense en soportes sólidos en la validación de delitos sexuales - Chávez Vera, Luis Fernando (2018)
Sexual crimes have increased alarmingly during last 5 years, therefore the collection of evidences, evidence analysis, and result reports from a forensic laboratory is essential in order to solve sexual crime cases. The techniques to evidence the existence of a sexual offense are P30 determination and Christmas the coloration technique. Both techniques are dependent to each other. When the two of the turn positive, the existence of rape is proven. The P30 technique is an inmunochromatographic method which is very specific because no external pathogenic factor alters the result; even when there is little sample concentration this technique can still detect this protein. The Christmas Tree coloration is a specific stain for the sperm and similar foreign artifacts do not stain the spermatozoon when using the method. According to the analysis of the 200 samples, it was verified that, the optimum temperature for the conservation of the samples is the refrigeration with a 55% humidity, so that the detection cache is 100% reliable .The sperm remains intact as long as it is freeze under -5°C or less temperature, and with a humidity 85%. The humidity is high (this is due to the thawing process that the sample undergoes). The rapid freezing and preservation environment cause the sperm to remain. Cellulose paper should be used to preserve it.All of them together help to increase a 98% reliable test result.